An Analysis of Expressive Illocutionary Act Found in Night School Movie - Ngurah, Si Made Ngurah Paramaartha; Komang Dian Puspita Candra (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
Abstract Language is an important aspect of communication that is used to interact, speak, and express feelings. Expressive speech acts are typically the facets of speech acts commonly employed in communication. This study examines the significance of expressive illocutionary acts in human communication, focusing specifically on the Night School movie. This study applies a qualitative descriptive approach. In this study, the concept of expressive illocutionary acts proposed by Searle (1979) is used as a theoretical framework that guides the investigations carried out. The purpose of this study is to identify and analyze the various expressive illocutionary acts performed by the characters in the Night School movie. The findings reveal six types of expressive illocutionary acts: thanking, apologizing, congratulating, wishing, attitude, and greeting. Through the application of pragmatics, the study offers insights into the interpretation and understanding of the communicative events within the film, highlighting the importance of expressive illocutionary acts in conveying emotions and shaping interpersonal dynamics. This research contributes to the broader field of pragmatics and provides a framework for analyzing expressive illocutionary acts in film. Keywords: pragmatics, expressive illocutionary act, night school movie